SERAPAN NITROGEN DAN BEBERAPA SIFAT FISIOLOGI TANAMAN PADI SAWAH DARI BERBAGAI UMUR PEMINDAHAN BIBIT ( NITROGEN UPTAKE AND SEVERAL PHYSIOLOGICAL CHARACTERS OF LOWLAND RICE FROM VARIOUS AGE SEEDLINGS) - Faozi, Khavid; Wijonarko, Bambang Rudianto (Pembangunan Pedesaan, 2010)
The research was conducted to study the appropriate age seedlings and suitable nitrogen fertilizer dose for increasing physiological characters and lowland rice yield. The research was a pot experiment in a plastic house, Faculty of Agriculture, Unsoed Purwokerto, from May to September Factors tested were the age of seedlings, i.e., 7, 14 and 21 days, and dose of nitrogen fertilizers, i.e., 0, 150, and 300 kg urea/ha. Variables observed were nitrogen uptake, nitrate reductase activity (NRA) of leaves, leaf chlorophyll content, leaf greenness, plant growth rate (LPT), net assimilation rate (LAB), plant dry weight, grain weight per clump, and harvest index. Observation data were analyzed by F test to determine the diversity and followed by Duncan Multiple Range Test (DMRT) and regression test at level 5% to determine the age of seedlings and the proper dose of nitrogen fertilizer. Result of the research showed that uptake of nitrogen in urea fertilizer treatment depended on the age of the seeds used. Age appropriate seed was 12.17 days with the weight of grain per clump maximum of 35.23 g. Fertilization of 300 kg urea/ha gave the best yield of 49.38 g of rice per clump compared to 150 kg urea/ha of 32.32 g or without fertilization of 16.42 g.